2021
DOI: 10.1021/acs.jafc.0c06337
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, Structure Characterization, and Antioxidant and Antibacterial Activity Study of Iso-orientin–Zinc Complex

Abstract: Flavonoid−metal complexes possess more effective functional properties than flavonoids. However, the research of iso-orientin (Iso)−metal complex has rarely been reported. In this study, Iso−zinc complex (Iso−Zn, [Zn 3 (C 21 H 14 O 11 ) 2 ]•4H 2 O) had been synthesized and characterized. From the UV−vis spectra and IR spectra, the 4-carbonyl group in the C-ring of Iso was involved in the metal chelation besides A-ring and B-ring hydroxyl group. Thermal gravimetric analysis and the water contact angle test show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Although several papers have reported or touched on the chelating effect of flavonoids toward Zn 2+ , , a direct comparison of a variety of flavonoids performed under the same conditions was lacking. This is particularly important since it was previously shown that chelation of Zn 2+ by flavonoids is significantly affected by pH , and the solvent used .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several papers have reported or touched on the chelating effect of flavonoids toward Zn 2+ , , a direct comparison of a variety of flavonoids performed under the same conditions was lacking. This is particularly important since it was previously shown that chelation of Zn 2+ by flavonoids is significantly affected by pH , and the solvent used .…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies performed to date on the chelation of Zn 2+ by flavonoids have reported chelation data only under noncompetitive conditions, e.g., when a flavonoid was mixed with Zn 2+ only, or the experiments have been performed alternatively in a buffer. Under such conditions, many flavonols (3-hydroxyflavones, kaempferol, quercetin, rutin, quercitrin, morin, myricetin, galangin, and fisetin) and several flavones (5-hydroxyflavone, 6,7-dihydroxyflavone, 3′,4′-dihydroxyflavone, chrysin, and luteolin), catechin, and taxifolin were reported to form a complex with Zn 2+ . ,, , Additionally, complexes of zinc with dihydroquercetin and isoorientin (luteolin-6-C-glucoside) were synthesized. These data do not seem to be in agreement with the current results, but on the contrary, they complement our information. This means that many flavonoids can form complexes with Zn 2+ , but their stability is low in most cases because they were not able to retain Zn 2+ in competition with another chelator, namely, the indicator dithizone used in our competitive method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus) and Escherichia coli (E. coli) were chosen as the target bacteria. Antibacterial activity can be calculated according to the number of bacterial colonies present on an agar culture plate. In this work, agar plate photographs and SEM images of the bacterial colonies formed by S.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of MRSA, the biofilm formation, different virulence factors like slime formation, EPS production, sliding and spreading ability, staphyloxanthin biosynthesis, α-hemolysin production, hydrophobicity, autoaggregation ability, etc., increase the pathogenicity and hence are responsible for drug-resistance, making it difficult for proper treatment. In this regard, there are several reports on the studies related to drug discovery, being carried out to develop new therapeutic approaches and effective drugs having a wide range of antimicrobial activities. , Usually, the infections involving in long-term drug administration are presently treated by employing oral or intravenous antibiotics. However, the infections that are associated with medical devices characterized by microbial biofilm formation on the device have resulted in prolonged delivery to the target site and drug decomposition as a consequence of other factors such as pH, temperature, and side-reactions with other compounds .…”
Section: Introductionmentioning
confidence: 99%